2006
DOI: 10.4049/jimmunol.177.6.3821
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Memory CD8 T Cell Development in the Absence of Methyl-CpG-Binding Domain Protein 2

Abstract: Intracellular differentiation events that determine which cells develop into memory CD8 T cells are currently incompletely understood. Methyl-CpG-binding domain protein 2 (MBD2) is a transcriptional repressor that binds to methylated DNA and mediates the biological consequences of epigenetic gene methylation. The role of MBD2 during the differentiation of naive CD8 T cells into effector and memory cells was determined following acute infection of MBD2-deficient mice with lymphocytic choriomeningitis virus. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 47 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…While we are unable to address the question of demethylation of the IFNG promoter as the targeted regions did not reach sufficient read depth in our analysis, high depth analysis of unstimulated naïve and memory cells from two donors showed that CD4 memory T cells are hypomethylated compared to naïve, suggesting that the demethylation of the IFNG promoter upon differentiation into effector cells is maintained following development of a CD4 memory phenotype. Interestingly, studies in murine CD8 T cells have demonstrated that the IFNG promoter and enhancer is hypermethylated in memory cells compared to effector cells, but is rapidly demethylated in response to antigenic stimulation (42, 43). Such differences between epigenetic regulation of single genes in CD4 and CD8 T cells highlights the importance of cell specific transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…While we are unable to address the question of demethylation of the IFNG promoter as the targeted regions did not reach sufficient read depth in our analysis, high depth analysis of unstimulated naïve and memory cells from two donors showed that CD4 memory T cells are hypomethylated compared to naïve, suggesting that the demethylation of the IFNG promoter upon differentiation into effector cells is maintained following development of a CD4 memory phenotype. Interestingly, studies in murine CD8 T cells have demonstrated that the IFNG promoter and enhancer is hypermethylated in memory cells compared to effector cells, but is rapidly demethylated in response to antigenic stimulation (42, 43). Such differences between epigenetic regulation of single genes in CD4 and CD8 T cells highlights the importance of cell specific transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX3, TNFRSF9, and MBD2 encode proteins involved in the generation of CD8 T cells. [53][54][55] Similarly, ETS1, IRF4, TAGAP, and B3GNT2 encode proteins involved in the activation and differentiation of CD8 T cells. 53,56,57 That ERAP1 codes for a protein that trims peptides in the endoplasmic reticulum before their MHC class I presentation, 58 and that it interacts with HLA-C indicates that this gene is important for antigen presentation.…”
Section: Antigen Presentationmentioning
confidence: 98%
“…A limiting DNA methylation affects the proliferative potential of Ag-specific CD8 + T cells with moderate effects on their differentiation to effector and memory CD8 + T cells (20). Additionally, methyl-CpG-binding domain protein 2-deficient mice display reduced memory CD8 + T cell differentiation following acute viral infection (21).…”
Section: Memory Cd4mentioning
confidence: 99%